2009
DOI: 10.1542/peds.2007-2825
|View full text |Cite
|
Sign up to set email alerts
|

School Recess and Group Classroom Behavior

Abstract: Three small studies have suggested that students without recess may have difficulty concentrating on specific tasks in the classroom, are restless, and may be easily distracted. What This Study AddsOur study examined the relationship between school recess and group classroom behavior in a nationally representative sample. This study showed that a break during the school day was associated with better TRCB scores. ABSTRACTOBJECTIVES. This study examines the amount of recess that children 8 to 9 years of age rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
146
2
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(164 citation statements)
references
References 11 publications
5
146
2
5
Order By: Relevance
“…[9][10][11] This is particularly concerning, because daily physical activity is not only essential for healthy weight maintenance, but also for practicing and learning fundamental gross motor skills [22][23][24][25] and socioemotional and cognitive skills. [26][27][28][29][30][31][32][33][34] In the United States, child care facilities are licensed by individual states. The primary purpose of state licensing codes is to protect the health and safety of children.…”
mentioning
confidence: 99%
“…[9][10][11] This is particularly concerning, because daily physical activity is not only essential for healthy weight maintenance, but also for practicing and learning fundamental gross motor skills [22][23][24][25] and socioemotional and cognitive skills. [26][27][28][29][30][31][32][33][34] In the United States, child care facilities are licensed by individual states. The primary purpose of state licensing codes is to protect the health and safety of children.…”
mentioning
confidence: 99%
“…According to the National Association of Early Childhood Specialists in State Department of Education (n.d.) there is a movement towards elimination of recess in many school districts in the United States despite evidence that supports a need for recess. Barros et al (2009) found that teachers rated classroom behavior of children who had no recess or only a minimal break lower than children with regular recess. Because it is difficult for children to learn in a disruptive classroom this suggests recess, or play, is important to achieving academic skills (Harrell & Hollins, 2009;Henninger & Cleman, 2008;Luiselli, Putnam, Handler& Feinberg, 2005).…”
Section: Lack Of Playmentioning
confidence: 97%
“…Children are now spending more and more time playing video games and participating in structured activities -such as organized sports and more academic based activities (Ginsburg, 2007;Wenner, 2009;Barros, Silber, & Stein, 2009). …”
Section: Lack Of Playmentioning
confidence: 99%
“…Es curioso que en esa misma línea por optimizar el rendimiento escolar haya gobiernos que se hayan planteado la supresión de este tiempo. Son varios los estudios que justifican su necesidad para el desarrollo social y cognitivo (PELLEGRINI; DAVIS, 1993, PELLEGRINI;SMITH, 1993;BOHN, 2005, BARROS;SILVER;STEIN, 2009). En la actualidad nos encontramos cada vez con más justificaciones desde el mundo de la pediatría y la lucha contra la obesidad infantil.…”
Section: Infierno Y Paraísounclassified